Evaluation of Passive Fire Protection Systems for Library and Service Buildings Archives of Indragiri Hulu Regency - Aldi Marzuliadi; Nedra Neswita; Sri Agustin (MultiTech Publisher, 2024)
The purpose of this research is to determine the evaluation of the protection system passive in fire prevention efforts in official buildings Library and Archives of Indragiri Hulu Regency, Riau Province. Data collection was carried out by observation, document review and interviews regarding passive fire protection systems in Service Buildings Library and Archives of Indragiri Hulu Regency, Riau Province. The results of this research are to show that the building has a passive fire protection system with assessment standards and the results of the conformity assessment against applicable standards, namely the Service Building Libraries and Archives have a score of 67.39%.